Бесы: [роман] / Федор Достоевский - Достоевский Федор Михайлович (Мировая классика, 2018)
Экземпляры: ЦБ (20190315) / Инвентарный номер: 50858 / Цена: 150.00 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: Д 70 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1-44